Haematological and biochemical profile of Mecheri sheep during winter and summer - SELVARAJ, P; MATHIVANAN, R; NANJAPPAN, K (The Indian Journal of Animal Sciences, 2014)
Influence of seasonal effect on hemato-biochemical parameters of Mecheri sheep was studied. No change in hematological values of RBC, WBC, Hb and ESR were observed during winter between preweaning, postweaning, 1-2 years and adult groups except for PCV. pev values were significantly (P